(untitled) (Strathmore Law Review, 2021)
The contemporary rise of terrorism as a form of violent extremism has led the government to adopt a narrow state-centric security approach to mitigate these threats. Violent extremism compromises peace, security, and communal cohesion, and often thrives on human security deficits such as marginalisation and disenfranchisement from the decision-making processes. The prominence of a state-centric security approach has overshadowed the human security dimension of countering violent extremism, thereby compromising state-society relations. On the contrary, a human security approach which entails freedom from fear and freedom from want, is viewed as a holistic approach to security that secures both the state and society. Less debated, however, is the relationship between countering violent extremism and societal marginalisation as viewed through the lens of human security. This paper argues that the narrow state-centric approach adopted by the Kenyan government in the Northern Frontier Counties has continually marginalised the community living in these counties and is proving unsustainable in countering violent extremism. As a point of departure from this approach, a more human security centred approach is suggested which is likely to be more sustainable in countering violent extremism and more successful in reversing the trend of marginalisation that has arisen from the narrow state-centric approach.